Post-Soviet urban renewal and its discontents : gentrification by demolition in Baku - Valiyev, Anar; Wallwork, Lucy (Routledge, 2019)
Gentrification is being increasingly discussed as a driver of urban change globally, including in the former Soviet Union. However, the translation of the gentrification phenomenon into post-Soviet cities like Baku remains poorly understood. This article explores how a particular form of state-led “gentrification by demolition” is unfolding in Baku. We assert the ongoing relevance of using the framework of gentrification to analyze the processes. We go on to use the case of the recently demolished Sovetsky district to carefully expand the geography of the gentrification discourse. We argue that Baku’s own “landscape of gentrification” is shaped by a number of preconditions. It bears the marks of the legacy of post-socialist cities. However, it more resembles muscular state-led “gentrification by demolition” that is characteristic of Chinese cities. It also echoes Soviet city-building legacies in its use of spectacle and “grand gesture” to legitimize and buy support for gentrification policies.
Urban Geography
Keywords: Gentrification -- Baku (Azerbaijan).; Gentrification -- Case studies.; Baku (Azerbaijan) -- Social conditions.